Formation Dynamics of BH and GaH‐Pairs in Crystalline Silicon During Dark Annealing. Issue 17 (9th July 2022) - Acker, Yanik; Simon, Jochen; Herguth, Axel
Abstract : In crystalline silicon, atomic hydrogen released from hydrogen dimers forms acceptor–hydrogen pairs during annealing in the dark at elevated temperatures. In this study, the formation of boron–hydrogen (BH) and gallium–hydrogen (GaH) pairs in 1 Ω cm silicon is investigated at temperatures ranging from 140 to 220 °C. Acceptor–hydrogen concentrations in the low 10 14  cm − 3 range are quantified by means of highly sensitive resistance measurements. GaH pairs are generally found to form faster than BH pairs. Arrhenius analysis shows a difference in activation energy (BH: 1.20 eV, GaH: 1.04 eV) while the trial frequency is the same ( ≈ 4 × 10 8  s − 1 ). Abstract : The formation of boron–hydrogen (BH) and gallium–hydrogen (GaH) pairs in the low 10 14  cm −3 range in boron‐ or gallium‐doped crystalline silicon during annealing in the dark at temperatures ranging from 140 to 220 °C is investigated by means of highly sensitive resistance measurements. An Arrhenius analysis reveals differences in formation dynamics.